Teknik perbanyakan massal parasitoid Anagrus nilaparvatae (Pang et Wang) (Hymenoptera: Mymaridae) dengan kotak plastik - Araz Meilin; Y. Andi Trisyono; Edhi Martono; Damayanti Buchori (Perhimpunan Entomologi Indonesia, 2012)
Anagrus nilaparvatae (Pang et Wang) is an egg-parasitoid of rice brown planthopper (Nilaparvata lugens Stål). The objective of this study was to develop a mass-rearing technique of A. nilaparvatae. Mass-rearing was done using a plastic box (14 cm × 18.5 cm × 18.5 cm, made of plastic-mica, the upper side equipped with a 10 cm test tube), placed on a tray with rice seedlings containing an estimated of 11,130 eggs of N. lugens. About 355 adult parasitoids were successfully released per box when each box was infested with 50 parasitoids. The number of parasitoids produced were reduced to 164 adults when the infestation was made at 100 parasitoids per box. The emergence of parasitoids started around 07:00 am until 04:00 pm with the highest rate (36.2%) occured at 10:00 am. One plastic box cost only Rp10.000,-; thus the estimate cost to produce one parasitoid using this tecnique was Rp60,- These findings suggest that the plastik box is a simple and inexpensive technique for mass-rearing of A. nilaparvatae.